INCIDENCE DYNAMIC OF POD ROT DISEASE OF COCOA CLONES IN LAMPUNG, INDONESIA - Evizal, Rusdi; ,, Sugiatno; ,, Ivayani; Pujisiswanto, Hidayat; Wibowo, Lestari; Erry Prasmatiwi, Fembriarti (Universitas Lampung, 2018)
Incidence dynamic of pod rot disease of cocoa clones in Lampung, Indonesia. The declining of production and productivity of cocoa in Indonesia might due to pests and diseases attacks and planting unselected clones. Dynamic of pod rot incidence was important to plan pest controlling. To study dynamic incidence of some cocoa clones, a research was conducting in Pesawaran District, a centre of cocoa production in Lampung. A farmer cocoa plot under agro-forestry system was selected which had been upgrading in 2014 by pruning and side-grafting with national clones including Sul 1, MCC 1, MCC 2, ICCRI 7 and selected local clone named T1, T2, and T3. The results showed that pod rot incidence occurred along the year of observation. For immature pod, pod rot incidence was dynamic and varied among months and clones. There was high pod rot incidence every months for particular clone. National clone Sul1 and local clone T3 exhibited more tolerant to pod rot disease than other clones. Clones Sul1 and T3 also produced more pod than others. High incidence of pod rot occurred on fruit stage of cherelle (incidence 38.7%) and small pod (incidence 18.8%) that well known as cherelle wilt symptom.